About the United Nations ... environment and development. - United Nations (New York United Nations Publications, 1992)
Olivia Newton John introduces the viewer to the work of the United Nations in undertaking to establish worldwide policies for environmental recovery.
You will see young people replanting trees in Tahiland, where unchecked logging led to catastrophis floods in 1988. In Polnad, teenagers work with the UNESCO sponsored Baltic Sea Project to reclaim the fragile ecosystem of a region that has suffered dacades of abuse.
The message of this film is hopeful: International cooperation and the concern of young and the concern of young people throughout the world can help to reclaim the environment for future generations.
Careless industrial practices in both the developed and developing world are destroying the future of the planet. This filmexplores some of the efforts that are being made to reverse this grim trend.
Keywords: Environmental Recovery